CONTROL SYSTEM IS AN APPLIED MATHEMATIC - Rohani Jahja Widodo (Website, 2014)
This paper presents developments and applications of Control Systems (CS) as an Applied Mathematic (AM). Several characteristics of CS can be linked to human behavior. CS can